A 3D Design Based on Jewelery Production Technology with Special Features - S. Gamov, E; B. Tonkovid, S; A. Kukushkina, V; A. Nikulcheva, N (International Journal of Engineering and Technology, 2018)
This article shows the process of development and manufacturing of the exclusive "Ring" product with application of modern technologies of its manufacturing. The main stages of the process of designing, modeling and getting the finished product are presents. Recommendations for the selection of software are given. The advantages of application of additive technologies in jewelry production are shown.Â